Cpx‐mediated amino acid sensing diversifies gastrointestinal colonization of Klebsiella pneumoniae - Danyang Li; Qiucheng Shi; Liuqing He; Jianhua Luo; Huajie Zhu; Xiaoting Hua; Yunsong Yu; Yan Jiang; Liang Tao (mLife)
Abstract Klebsiella pneumoniae is a Gram‐negative opportunistic pathogenic bacterium that occasionally inhabits the human gastrointestinal tracts. Gut‐colonized K. pneumoniae may then metastasize to other organs and tissues, thus causing severe infections. In this study, we identified three cpxA mutations in K. pneumoniae that experimentally evolved to show reduced adhesive ability. CpxA is a sensor histidine kinase that rendered reduced surface adhesion and gut colonization ability in K. pneumoniae. Interestingly, one experimentally gained CpxA mutant (L168del) also commonly occurs in nature. K. pneumoniae containing CpxA variants showed different colonization potentials through altered type 3 fimbriae expression. Lastly, we demonstrated that CpxA contributes to amino acid sensing, thus regulating the colonization of K. pneumoniae both on solid surfaces and in mouse intestines. The polymorphism of CpxA may help to broaden the environmental adaptation of the bacterium. These findings together reveal a Cpx‐mediated regulation to diversify intestinal colonization in K. pneumoniae.